Mapping the flow of commercial broiler day-old chicks in Kenya - Ibayi, Eugine L.; Nyambura, Jane N.; Guyo, Boru A.; Moodley, Arshnee; Muloi, Dishon M. (Frontiers Media, 2025)
Introduction: Poultry production is a significant contributor to economic growth and food security in Kenya. Reliable data on day-old chicks (DOCs) production and distribution are essential for formulating effective national policies on poultry production and animal health delivery. Here, we describe the commercial broiler DOCs production, distribution, and associated animal health and antibiotic use practices in Kenya.